143 Effect of Supplementary Selenium Source on Dairy Cow Performance, Antioxidant Status, and Apparent Absorption and Retention. (8th October 2021) - Cruickshank, Keira M; Hatew, Bayissa; Gehman, Amanda M; Koenig, Karen M; Ribeiro, Eduardo S; Steele, Michael A
Abstract: The objective of this experiment was to determine how source of selenium (Se) affects dairy cow performance, antioxidant status, and apparent absorption and retention. Multiparous Holstein cows (n = 24; 597 ± 49 kg BW) were blocked by days in milk (161 ± 18) and randomly assigned to receive 0.3 mg/kg of either: 1) organic Se (selenized yeast; ORG; Sel-Plex-Alltech); or, 2) inorganic Se (sodium selenite; INO) premix, top dressed and mixed into a ration daily. After an 11-week adaptation period (blood and milk sampled monthly), cows received an intraruminal dose of Se 77 (either Se 77 yeast or NaSe 77 O3 ) followed by a 4-day period of blood and rumen fluid sampling, and total collection of feces, urine, and milk. Data were analyzed using PROC GLIMMIX in SAS with fixed effects of treatment, time, and their interaction, and random effect of block. Daily DMI (23 ± 0.6 kg), milk yield (35 ± 1.2 kg), plasma glutathione peroxidase (64 ± 4.2 U), and serum Se (0.11 ± 0.003 µg/g) were not different between treatments during the adaptation period. Serum Se 77 maximum concentration and area under the curve (AUC) were not different between treatments for 72 hours following infusion, but rumen fluid Se 77 AUC was higher (P = 0.02) for ORG cows. Apparent absorption (64 ± 1.3%) and retention (44 ± 1.5%) of the Se 77 dose did not differ between treatments. The ORG cows had lower urinary excretion (13 vs. 17 ± 0.6%; P < 0.01), higher milk excretion (6 vs. 2 ± 0.3%; P < 0.01), and similar fecal excretion (36 ± 1.3%; P = 0.9) of Se 77 compared to INO cows. These results indicate that ORG Se increased Se content of milk and decreased Se excretion in urine, but did not alter performance, antioxidant status, and apparent absorption and retention of Se in mid-lactation cows.